SOCIO-ENVIRONMENTAL FUNCTION OF THE CITY: ANALYSIS OF THE VEGETATION COVER OF THE JARDIM DAS OLIVEIRAS NEIGHBORHOOD IN SENADOR CANEDO/GO (CIPEEX, 2025)
The study analyzes the socio-environmental function of cities through vegetation cover in the Jardim das Oliveiras neighborhood, in Senador Canedo/GO, between 2002 and 2024, investigating the impacts of disordered urbanization. The central problem is the significant reduction in green areas, which directly affects environmental quality and the well-being of the local population. Uncontrolled urbanization has led to soil sealing, an increase in heat islands and a loss of biodiversity, compromising the right to a sustainable city. The general objective is to analyze the changes in the neighborhood's vegetation cover over this period, considering its importance for the environment and the quality of life of residents. The specific objectives include: (a) examining the urbanization process in Brazil and its socio-environmental and legal consequences; (b) investigating Brazilian urban policy, with an emphasis on the Statute of Cities; (c) exploring the use of geotechnologies as a tool for sustainable urban planning; (d) evaluating the socio-environmental function of the city based on vegetation cover; and (e) characterizing the socio-spatial evolution of Jardim das Oliveiras between 2002 and 2024. The methodology adopted combines qualitative and quantitative methods, with analysis of satellite images, review of legal documents, field surveys and the use of geotechnologies to map transformations in vegetation cover. The justification for the research lies in the urgent need to rethink urban planning, faced with the challenges of disorderly urbanization and the loss of green areas, which are essential for climate regulation, air quality and leisure for the population. The analysis revealed a worrying trend in the reduction of green areas in the neighborhood, with serious environmental implications such as increased flooding and deteriorating air quality. In addition to the ecological impacts, the lack of green spaces compromises residents' quality of life, limiting opportunities for recreation and outdoor living. The results indicate that although Brazilian legislation and urban planning instruments, such as the City Statute, establish guidelines for the preservation of green areas, the practical implementation of these policies is ineffective in Senador Canedo. The research highlights the importance of reformulating the municipality's Master Plan, integrating environmental criteria that prioritize the conservation and expansion of green areas, as well as promoting greater community participation and the use of technologies for sustainable urban planning.